Randomized trial of primary PCI with or without routine manual thrombectomy - Jolly, Sanjit S; Cairns, John A; Yusuf, Salim; Meeks, Brandi; Pogue, Janice; Rokoss, Michael J; Kedev, Sasko; Thabane, Lehana; Stankovic, Goran; Moreno, Raul; Gershlick, A. H; Chowdhary, Saqib; et al. (The New England journal of medicine, 2015)
BACKGROUND: During primary percutaneous coronary intervention (PCI), manual thrombectomy may reduce distal embolization and thus improve microvascular perfusion. Small trials have suggested that thrombectomy improves surrogate and clinical outcomes, but a larger trial has reported conflicting results. METHODS: We randomly assigned 10,732 patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary PCI to a strategy of routine upfront manual thrombectomy versus PCI alone. The primary outcome was a composite of death from cardiovascular causes, recurrent myocardial infarction, cardiogenic shock, or New York Heart Association (NYHA) class IV heart failure within 180 days. The key safety outcome was stroke within 30 days. RESULTS: The primary outcome occurred in 347 of 5033 patients (6.9%) in the thrombectomy group versus 351 of 5030 patients (7.0%) in the PCI-alone group (hazard ratio in the thrombectomy group, 0.99; 95% confidence interval [CI], 0.85 to 1.15; P=0.86). The rates of cardiovascular death (3.1% with thrombectomy vs. 3.5% with PCI alone; hazard ratio, 0.90; 95% CI, 0.73 to 1.12; P=0.34) and the primary outcome plus stent thrombosis or target-vessel revascularization (9.9% vs. 9.8%; hazard ratio, 1.00; 95% CI, 0.89 to 1.14; P=0.95) were also similar. Stroke within 30 days occurred in 33 patients (0.7%) in the thrombectomy group versus 16 patients (0.3%) in the PCI-alone group (hazard ratio, 2.06; 95% CI, 1.13 to 3.75; P=0.02). CONCLUSIONS: In patients with STEMI who were undergoing primary PCI, routine manual thrombectomy, as compared with PCI alone, did not reduce the risk of cardiovascular death, recurrent myocardial infarction, cardiogenic shock, or NYHA class IV heart failure within 180 days but was associated with an increased rate of stroke within 30 days. (Funded by Medtronic and the Canadian Institutes of Health Research; TOTAL ClinicalTrials.gov number, NCT01149044.).
Keywords: Female; kardiovaskulární nemoci; lidé středního věku; Percutaneous Coronary Intervention; elektrokardiografie; Kaplanův-Meierův odhad; koronární angioplastika; mužské pohlaví; Humans; Microvessels; infarkt myokardu; Electrocardiography; kombinovaná terapie; Cardiovascular Diseases; Kaplan-Meier Estimate; trombektomie; Stroke; srdeční selhání; lidé; Middle Aged; cévní mozková příhoda; senioři; Coronary Thrombosis; ženské pohlaví; Combined Modality Therapy; Thrombectomy; Aged; Heart Failure; mikrocévy; Male; koronární trombóza; Myocardial Infarction